No direct coupling between bending of galaxy disc stellar age and light profiles as seen from CALIFA. Issue Volume 11:Issue S321(2015) (21st March 2017) - Ruiz-Lara, Tomás; Pérez, Isabel; Florido, Estrella; Sánchez-Blázquez, Patricia; Méndez-Abreu, Jairo; Lyubenova, Mariya; Falcón-Barroso, Jesús; Sánchez-Menguiano, Laura; Sánchez, Sebastián F.; ,
Abstract : Recent theoretical and observational works claim the existence of galaxies with a characteristic age profile consisting on a negative radial trend followed by a smooth age upturn in its outskirts ("U-shape"). This shape has been generally related to down-bending light distributions; however, the existence of a real link between observed Surface Brightness (SB) profiles and changes in stellar properties such as age is still unclear.